Perlindungan Konsumen atas Kasus Pembobolan Akun di E-Commerce Tokopedia - Rizqi Nur Safitri; sabrina rizki puspitasari; Zafirah Aurelia Budiman (Jurnal Hukum Lex Generalis, 2026)
This study examines the liability of electronic transaction business actors for consumer account breaches and the legal consequences arising from violations of consumer rights due to personal data breaches on the Tokopedia e-commerce platform. The purpose of this study is to analyze the legal responsibilities of business actors for failures in protecting consumers' personal data and to examine the legal consequences arising from such breaches. This research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that Tokopedia, as a business actor and electronic system provider, has a legal obligation to protect consumers' personal data in accordance with applicable laws and regulations. The personal data breach resulted in the violation of consumers' rights to security, comfort and personal data protection, and may cause both material and immaterial losses to consumers. Furthermore, the enactment of Law Number 27 of 2022 concerning Personal Data Protection has strengthened legal protection for consumers as data subjects.